Increased Risk of Injury Following a Diagnosis of Vertigo: A Population‐based Study. (18th March 2021) - Yang, Tzong‐Hann; Xirasagar, Sudha; Cheng, Yen‐Fu; Wang, Chia‐Hui; Lin, Herng‐Ching
Abstract : Background: This study aimed to evaluate whether peripheral vestibular disorders (PVD) are associated with subsequent injury. Methods: Data for this follow‐up study were retrieved from the Taiwan's National Health Insurance (NHI) Dataset. A total of 251, 355 patients with newly diagnosed PVD during January 2015 to December 2016 was identified as the study cohort, the diagnosis date being their index date. Comparison patients were identified by propensity score‐matching (one per case, n = 251, 355 controls) from the remaining NHI beneficiaries in 2015 with their index date being the date of their first health service claim in 2015. We tracked each subject's claims history for 1 year from the index date to identify those who suffered an injury. Cox proportional hazards regressions were performed to calculate the injury hazard ratio of cases versus controls. Results: The incidence of injury during 1‐year follow‐up was 128.6 (95% CI = 127.6–129.5) per 1, 000 person‐years, 158.2 (95% CI = 156.8–159.6) and 97.5 (95% CI = 96.3–98.7) among the study and comparison cohorts, respectively. After adjusting for demographic variables, the hazard ratio (HR) for injury during 1‐year was 1.663 (95% CI: 1.636–1.690) for cases relative to controls. Conclusions: Patients with PVD were at a higher risk for a wide range of injuries, most of all, joint dislocation and sprain. Level of Evidence: 3 Laryngoscope, 131:1633–1638, 2021